Fire Safety and Prevention Issues in Design of Tall Buildings - Yılmaz, Didem Güneş (International Journal of Architectural Engineering Technology, 2022)
Fire safety design of tall buildings is crucial. The number of floors, the function, and the occupants’ features build the complexity in the life and fire safety design of tall buildings. Because of the complexity of each tall building design, specific preventive measures are necessary more than the basic requirements given in the national and local codes. The fire safety design of the world-renowned tall buildings, including Guangzhou International Finance Centre (IFC), Capital Market Authority (CMA) Tower, and Jin Mao Tower are case studies and further focus is made on the facade design of tall buildings. The paper reviews the safety design issues and focuses on the fire evacuation models, estimations, and the effect of different parameters in the success of fire safety design of tall buildings. In addition to the various fire evacuation suggestions, the effect of human behavior in fire is also discussed through the literature review. Fire safety is not only an engineering problem to deal with, but also architects must know the holistic approach in the fire safety design of tall buildings since it involves their architectural design as well. The paper aimed to bring the most arguable issues in the fire safety design of tall buildings together and to highlight the value of different perspectives in achieving a promising fire safety design.